Static converter: didactic support software - de Oliveira, Luis Carlos Origa [UNESP]; Pennafiel, Uilson Ruas [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1994)
Teaching a course of special electric loads in a continuing education program to power engineers is a difficult task because they are not familiarized with switching topology circuits. Normally, in a typical program, many hours are dedicated to explain the thyristors switching sequence and to draw the converter currents and terminal voltages waveforms for different operative conditions. This work presents teaching support software in order to optimize the time spent in this task and, mainly to benefit the assimilation of the proposed subjects, studying the static converter under different non-ideal operative conditions.
Keywords: Computer simulation; Computer software; Electric currents; Electric loads; Electric network topology; Electric power systems; Electric waveforms; Mathematical models; Object oriented programming; Static converters; Switching circuits; Thyristors; Computer aided didactic resources; Converter currents; Switching topology circuits; Terminal voltages waveform; Computer aided instruction